NATIVE AND NONNATIVE DOGMAS AS PRECURSORS OF VALUE EDUCATION: INDIAN TEACHER EDUCATORS’ ATTITUDE TOWARDS DEVELOPMENT AND IMPLEMENTATION OF VALUE EDUCATION IN TEACHER EDUCATION - Paleeri, Sankaranarayanan (PEOPLE: International Journal of Social Sciences, 2017)
Value development of individuals is routed on the native culture. The native dogmas of axiology create the most suitable values of a society. This paper explores the teacher educators’ perception on native and nonnative dogmas as precursors of value education. Major objectives of the study are to find out whether Indian Teacher Educators’ attitude towards implementing value education in teacher education is favorable or unfavorable and to identify teacher educators’ discernments on value education that precursor the native and nonnative dogmas. Sample is 208 teacher educators of South India. Attitude scale, inventory and interview are the tools used. Quantitative and qualitative methods were used for analyses. It is found out that teacher educators have favourable attitude towards implementing value education. The discernments of teacher educators is that native dogma based value education enhances better value quintessence. More than 80% of teacher educators support the value education that based on native dogmas. 10% has neutral attitude and 8.65% supports nonnative dogmas. The paper suggests development of value education based on native dogmas. It also suggests development of value education from indigenous value concepts to international value theories.